Super-refractory status epilepticus in a 29-year-old pregnant female. (March 2021) - Carrasco, Cinthya; Schwalk, Audra; Hwang, Byungkwan; Iwuji, Kenneth; Islam, Ebtesam
Super-refractory status epilepticus is a rare medical and neurological emergency due to the high mortality and morbidity associated with this condition. Furthermore, there is very little data regarding its incidence, etiology, and management in the pregnant population with super-refractory status epilepticus. The treatment of super-refractory status epilepticus during pregnancy is specifically a major challenge as there are limited available therapeutic options due to the well-established teratogenicity of most antiepileptic drugs and the unknown safety profile of some of the anesthetics commonly used for seizure control. We report a case of successfully treated super-refractory status epilepticus in a 29-year-old, 26 weeks pregnant female who after an emergent delivery and prolonged exposure to multiple antiepileptic drugs recovered full neurological function.